Efficient searching for vector in code book - Ткаченко, О. М.; Феферман, О. Д.; Хрущак, С. В. (Problems of Informatization and Control, 2007)
In given article is considered process of the compaction language signal with use the vector code books. The Designed method of the adduction in order vector in code book, which is based on using the theories mazorization and method of the shaping window searching for of the vector in outline code book. Experimental study of the designed methods is Organized